The Construction of the Role of Single Father and the Internalization of Family Values in Waleed El Halfawy's Drama Series Catalog - Marsha Meliana Putri; Nurlinah; Resa Restu Pauji (Raja Zulkarnain Education Foundation, 2026)
This research is motivated by the growing representation of literature in visual media, especially digital drama series, as a medium for conveying character values in the family. The digital drama series Catalog by Waleed El Halfawy presents a new construction of the single father figure in the context of contemporary Arab culture which is still rarely studied and is seen as containing various aspects related to family values. This study aims to analyze visual and verbal signs in constructing the role of a single father and describe the internalization of family character values contained in the digital drama series Catalog. The theory used is Charles Sanders Peirce's triadic semiotics through the relationship of representamen, objects, and interpretants, which is combined with Syamsul Kurniawan's character education theory. This study uses a descriptive-qualitative method with a note-taking technique as the main method of data collection based on time triangulation. The results of the study found twenty-three relevant scene data from eight episodes, with four internalized family values, namely the value of honesty in four data, the value of discipline in two data, the value of hard work in five data and the value of responsibility in twelve data. This study concludes that the drama series Catalog represents the transformation of the role of a single father from an absent figure to an actively present figure, while also functioning as a medium for representing family character values in the context of contemporary Arab culture.